Eco-innovation, Responsible Leadership and Organizational Change for Corporate Sustainability - Dorel Mihai Paraschiv; Estera Laura Nemoianu; Claudia Adriana Langă; Tünde Szabó (Amfiteatru Economic)
Creating a sustainable development strategy is essential for organizations that seek to reduce risks associated with tightening legislation, increased energy prices and natural resources and growing customer demands. Sustainability requires the full integration of social and environmental aspects into the vision, culture and operations of an organization, a profound process of organizational change being essential. The purpose of this paper is to present the main drivers of corporate sustainability, illustrating – after a thorough literature review – the link between the following elements: corporate sustainability – a necessity in the current global context; eco-innovation – as a way to implement sustainability in an organization; responsible leadership – as the art of building and maintaining strong and moral relationships with all stakeholders; organizational culture and organizational change – the basic elements through which organizations continuously renew their processes and products, adapting them to the new context. Furthermore, the paper provides an overview of organizations active in Romania in terms of sustainability practices, in general, and the ecological component of sustainable development, in particular, by presenting the results of an exploratory questionnaire-based research. The research reflects the importance of visionary management in adopting and implementing sustainability in the responding organizations.